EFEKTIVITAS SISTEM PENGANGKUTAN IKAN NILA (Oreochromis sp) UKURAN KONSUMSI MENGGUNAKAN SISTEM BASAH, SEMI BASAH DAN KERING - mariun nani; zainal abidin; bayu setyono (Universitas Sriwijaya, 2015)
ABSTRACT The aim of study was to test three systems of live fish transportation for size consumption of Nile (Oreocromis sp.). The systems were wet system, semi-wet system, and dry system, with the main measured parameter was survival rate. The experiment used Completely Randomized Design with three different treatments of transportation systems. Each treatment replicated six times. Tested fish was nile with weight of 200 g, which was transported for two hours. Analysis of varians show that survival rates of nile during transportation were 100% and not different for all treatments (p> 0,05).After rearing for 5 days, nile for wet system and semi-wet system had no different survival rate (p> 0,05), 96,66% and 93,88 % respectively, and higher (p<0,05) than dry sistem survival rate 27,22%. Â Keywords : nile, survival rate, live fish transport system